FAKTOR-FAKTOR HARAPAN ORANG TUA YANG TIDAK REALISTIS TERHADAP ANAK: TINJAUAN PUSTAKA SISTEMATIS - Asri Florencia; Imronah; Jonathan Hutapea; Octavia Putri Nurcahyanie (Jurnal Binagogik, 2024)
This article describes the results of a study of articles published within the last ten years along withprimary sources without limitations on the year of publication. The specific aim of this study is toanalyze the impact that children experience from their parents' unrealistic expectations. Researchersconducted a study using systematic literature observations by collecting several relevant researchresults. Search for articles using rabbit research on the Semantic Scholar and Google Scholar databases.Based on the findings through meta-analysis using PRISMA, there were six articles selected for furtherstudy, and it was possible to identify three aspects of unrealistic parental expectations that had animpact on: 1. Mental health, 2. Academic performance, and 3. Academic achievement. The results ofthis empirical study provide an overview of the impacts that most parents, especially in Indonesia, needto pay attention to in order to be more concerned and able to adjust expectations to the child'sexpectations, competencies and development phase. Apart from that, attention is needed for researchersto study further the concept and the correlation of variables which is still limited.